TOBACCO ISSUES IN THE NORTHEAST: CONFRONTING THE CHALLENGES PERSENTED BY THE MASSACHUSETTS TAX INITIATIVE (Tufts Archival Research Center, 2007)
Confidential; Report on Tobacco Institute program adressing the effects on Northeastern states' legislative and local governments from the voter approval of a 25 cent tobacco tax increase in Massachusetts. Aims to encourage disbursement of the tax revenues for educational goals, to implement a regional legislative program to manage the new tax, and to address increased activity from local anti-smoking coalitions.